A Web Portal for Communicating Polygenic Risk Score Results for Health Care Use—The P5 Study - Marjonen, Heidi; Marttila, Minttu; Paajanen, Teemu; Vornanen, Marleena; Brunfeldt, Minna; Joensuu, Anni; Halmesvaara, Otto; Aro, Kimmo; Alanne-Kinnunen, Mervi; Jousilahti, Pekka; Borodulin, Katja; Koskinen, Seppo; et al. (Frontiers in Genetics, 2021)
We present a method for communicating personalized genetic risk information to citizens and their physicians using a secure web portal. We apply the method for 3,177 Finnish individuals in the P5 Study where estimates of genetic and absolute risk, based on genetic and clinical risk factors, of future disease are reported to study participants, allowing individuals to participate in managing their own health. Our method facilitates using polygenic risk score as a personalized tool to estimate a person’s future disease risk while offering a way for health care professionals to utilize the PRS as a preventive tool in patient care.